EVALUASI KERUSAKAN BANGUNAN AKIBAT GEMPA DI INDONESIA - Pinondang Simanjuntak (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2020)
Earthquake Resistant Building is the main requirement for Indonesian people because Indonesia is earthquake risk prone. Surveying showed that every earthquake in Indonesia caused many material losses and fatalities. Therefore the concept of earthquake resistant building is the main requirement for community and building construction practices. There are four components that affect the performance of earthquake resistant buildings: Strength, Stiffness, Ductility and Configuration of building structures. These need to be socialized to be understood correctly so that people understand the concept of earthquake resistant buildings. Based on the observations in various regions and compared to earthquake resistant building standards and concepts, it can be shown that the failure of building structures occurs due to the poor connection details of the structural elements and structural rigidity configuration of structure elements are not in a single entity,sturdy and compact. This paper discibes some of the basics theory of earthquake resistant and standards of SNI 03-1726-2012 and it compared to the pattern of damage of the structural elements due to earthquake. Comparison of that theory to the survey results show that the damage is due to the implementation in the field is not the same as result of the concept of theory and standards of earthquake resistant buildings regulations SNI 03-1726-2012. For this reason, it is recommended to conduct a socialization program and training in the construction of earthquake-resistant buildings to the community and to building practitioners, especially the builders and foremen Hopely that the implementation of the program can reduce the risk of material and life loss due to the earthquake in Indonesia.